Novel primary amine diazeniumdiolates—Chemical and biological characterization. Issue 3 (2nd May 2018) - Puglisi, Melany P.; Bradaric, Michael J.; Pontikis, John; Cabai, Jonathan; Weyna, Theodore; Tednes, Patrick; Schretzman, Robert; Rickert, Karl; Cao, Zhao; Andrei, Daniela
Abstract: Hit, Lead & Candidate Discovery Diazeniumdiolates, also known as NONOates, are extensively used in biochemical, physiological, and pharmacological studies due to their ability to release nitric oxide (NO . ) and/or their congeneric nitroxyl (HNO). The purpose of this work was to synthesize a series of primary amine‐based diazeniumdiolates as HNO/NO donors and to determine their efficacy as anticancer and antifungal agents in vivo. The seven compounds (3a‐3g ) were successfully synthesized and characterized, one of which had been previously reported in the literature (3g ). Two compounds showed anti‐proliferative effects against ovarian (ES2 and SKOV3) and AML monocyte‐derived cancer cells (THP‐1) when tested with standard MTT assays. Compounds3a and3g demonstrated reduced ovarian cancer cell proliferation when treated at doses from 0.033 to 1.0 mg/mL at the 24 hr time point. These compounds also exhibited moderate and selective antifungal activity against Fusarium oxysporum f.sp. lycopersici, one cause of opportunistic infections of immunocompromised patients, inhibiting the growth of the fungi at LD50 at 10 mg/mL. A third compound (3e) did not exhibit similar activities, possibly due to the alkyl chain. Our results suggest that the primary amine diazeniumdiolates may offer a versatile platform for the development of HNO/NO donors for biomedical applications.